Treatment of Diaphyseal Tibial Fractures Distal to a Total Knee Arthroplasty by Intramedullary Nailing Is Safe and Effective. Issue 12 (December 2022) - Shaath, Mohamed Kareem; Avilucea, Frank R.; Kerr, Matthew; Young, Everett; MacKenzie, Ronald; Langford, Joshua R.; Haidukewych, George J.
Abstract : Objectives: To report the clinical result of a series of patients who underwent intramedullary nailing (IMN) of tibial shaft fractures distal to a total knee arthroplasty (TKA). Design: Retrospective case series. Setting: Level-1 trauma center. Patients/Participants: Patients who sustained a tibial shaft fracture distal to a TKA treated with an IMN. Intervention: IMN of tibial shaft fractures distal to a TKA. Main Outcome Measurements: Postoperative weight-bearing status, readmissions, and complications or failure of treatment within 90 days; Knee Injury and Osteoarthritis Outcome Scores at the final follow-up; failure of treatment; and revision surgery. Results: Nine patients were included. The average age was 71.4 years (range 55–87 years). All TKAs were cemented. The average distance between the tibial keel and the cortical density of the tibial tubercle was 24.1 mm (range 19.5–26.7 mm). Six nails were inserted using an infrapatellar portal, 2 were inserted using a suprapatellar portal, and 1 was inserted using a lateral parapatellar approach. The median nail diameter was 10 mm (range 9–12 mm). All fractures were healed at the final follow-up. There were no infections or arthroplasty-related complications. Knee Injury and Osteoarthritis Outcome Scores ranged from 100% to 74% (median 82%). Conclusion: Overall, we report on the largest cohort in the literature undergoing IMN of a tibial shaft fracture distal to a TKA. We demonstrate that IMN of diaphyseal tibial fractures distal to a TKA can be performed safely. We additionally demonstrate that this treatment is highly effective in achieving fracture union with no arthroplasty-related complications. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.